Impact of the COVID-19 pandemic on breast surgery in a reference service for breast cancer treatment - Tiago, Luiza Herdy Boechat Luz; Moro, Carolina Dalla Santa Dal; Nunes, Carolina Odorizzi Magno; Vivian, Fernando; Azevedo, Karine Santos de; Damo, Marília; Lana, Marjoriê Aparecida Dalla; Ribeiro, Thaís Hunoff (Mastology, 2024)
Introduction: The pandemic caused by the spread of the SARS-CoV-2 virus posed unprecedented challenges to health systems and societies worldwide. Among the greatest challenges was the importance of balancing the treatment of patients with potentially lethal diseases alongside the pandemic. Treatment for breast cancer, a time-dependent disease, was also compromised, as financial resources, supplies, medicines, and, especially, hospital beds needed to be allocated to assist those infected with the new coronavirus. Surgeries were suspended and surgical centers closed. To compare the number of breast surgical procedures before and during the pandemic and assess their impact on the proportional number of surgeries performed. Methods: This is a retrospective cohort study, reviewing procedures recorded from January 2015 to June 2021. Results: A total of 899 patients were included, the majority of whom were female; 58.5% of cases were oncological. The most prevalent surgery in both periods was conservative oncology (sectorectomy or quadrantectomy). There was a significant difference in the number of procedures performed before and during the COVID-19 outbreak, with a 43% drop during the pandemic. There was no significant difference in the pattern of surgeries. Conclusion: The pandemic caused a significant reduction in the total number of elective surgical interventions in the period analyzed — a delay that the literature identifies as a potential risk factor for disease progression and increased death rates.